Effectiveness of a microsurgery training program using a chicken wing model. Issue 4 (1st August 2022) - Dave, Aniket; Singhal, Maneesh; Tiwari, Raja; Chauhan, Shashank; De, Moumita
Abstract: Microsurgical skills are essential for plastic surgeons in the modern times. Chicken wing model for microsurgery training offers an easy and cost-effective alternative to the traditional live rat model. A prospective study was conducted over a period of 6 months. Fifteen resident doctors in the department of plastic surgery were enrolled. Each of them underwent one session of microsurgery training on chicken wings (ulnar artery) every week for 15 weeks. The pre-training and post-training microvascular anastomosis were recorded and analyzed by two blinded investigators using a modification of the Structured Assessment of Microsurgery Skills (SAMS) tool. The pre- and post-training scores were compared. Twelve residents completed the requisite number of training sessions and were included in the final analysis. The mean diameter of the chicken wing ulnar artery was 1.04 mm (SD:0.11). All trainees demonstrated an improvement in the total scores. There was significant improvement in the mean scores (Pre-training: 33.46 vs. post-training: 41.42, p = 0.002). There was also a significant decrease in the total number of errors (Pre-training: 6.75 vs. post-training: 4.79, p = 0.012). However, there was no significant improvement in the average time taken to perform anastomosis (Pre-training: 58.03 mins vs. post-training: 52.51 mins, p = 0.182). We concluded that chicken wing is a useful training model for microsurgery. It helps in improving the overall microsurgical skill as well as reducing the average number of errors. This model is cost-effective, easily available, and easy to set-up. The wide assortment of vessels with varying diameters provides opportunities for training of microsurgeons of different skill levels.